Proceedings of the International Conference on Computer-Aided Design 2018
DOI: 10.1145/3240765.3240808
|View full text |Cite
|
Sign up to set email alerts
|

Fast FPGA emulation of analog dynamics in digitally-driven systems

Abstract: In this paper, we propose an architecture for FPGA emulation of mixed-signal systems that achieves high accuracy at a high throughput. We represent the analog output of a block as a superposition of step responses to changes in its analog input, and the output is evaluated only when needed by the digital subsystem. Our architecture is therefore intended for digitally-driven systems; that is, those in which the inputs of analog dynamical blocks change only on digital clock edges. We implemented a high-speed lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…There is unfortunately only one published result for the emulation performance of a fully-virtualized high-speed link: our own study from ICCAD 2018 [10]. That study, which preceded development of our emulation framework, showed that a variable timestep approach was promising for emulating high-speed links.…”
Section: A Dragonphymentioning
confidence: 97%
See 3 more Smart Citations
“…There is unfortunately only one published result for the emulation performance of a fully-virtualized high-speed link: our own study from ICCAD 2018 [10]. That study, which preceded development of our emulation framework, showed that a variable timestep approach was promising for emulating high-speed links.…”
Section: A Dragonphymentioning
confidence: 97%
“…Emulating AMS designs on those platforms, or even on off-the-shelf FPGA boards, requires that analog blocks are replaced by synthesizable models. A wide variety of strategies for doing just that have been reported, covering applications such as power conversion [8], [9], high-speed communication [10], [11], signal conditioning [12], [13], analog-to-digital conversion [14], and analog testing [15]. Reported speedups typically ranged from two to three orders of magnitude as compared to CPU-based simulation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations